Priapism Low-Flow Degree in Patient with Chronic Myeloid Leukemia (CML) - Mahlevi, Dea Syafira; Diansyah, M. Noor; Savitri, Merlyna; Amrita, Putu Niken Ayu; Romadhon, Pradana Zaky; Ashariati, Ami; Yudho Bintoro, Siprianus Ugroseno (Journal of Neonatal Surgery, 2025)
Background: Chronic Myeloid Leukaemia (CML) is a type of cancer caused by disruption of haematopoietic stem cells. CML is a type of Myeloproliferative Neoplasm (MPN). CML is caused by a cytogenetic abnormality involving chromosome 9 and chromosome 22, known as Philadephia (Ph) Chromosome. Case report: A 25-year-old male patient has been diagnosed as Chronic Myelous Leukaemia (CML) for 2 years 2019. The patient has been tested for BCR-ABL1 Quantitative PCR with 63% (IS) results in 2019. Previously, the patient received imatinib but from 2019 to 2021 the patient did not take the medicine regularly. the patient came to the hospital to find that the penis had an erection for 6 hours continuously. Based on anamnesis, physical examination and supporting examination in the form of complete blood, peripheral blood smear, and intracavitary blood gas analysis, we diagnosed the patient with Chronic Myeloid Leukemia (CML) with accelerated phase accompanied by leukostasis manifesting priapismus (ischemic). As initial management, the patient was given rehydration therapy, imatinib mesylate, hydroxyurea, analgesics, Xanthin oxidase and leukoferesis. Leukoferesis was performed once. Priapismus in the patient reduced slowly during the 14-day treatment Conclusion: Reported a case of a patient with Chronic Myeloid Leukemia (CML) experiencing priapismus with a low flow degree that improved with the administration of imatinib mesylate, hydroxyurea, analgesics, Xanthin oxidase and leukoferesis. Leukoferesis was performed once. The patient's urologist performed intracavernous aspiration and distal shunting with the ebbehoj method.